Pengaruh Literasi Keuangan dan Penggunaan Informasi Akuntansi terhadap Kinerja Keuangan UMKM dengan Peran Pembiayaan sebagai Variabel Moderasi - Fenita Zahrani Trisna Putri; Suwandi Suwandi (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of financial literacy and the use of accounting information on the financial performance of Micro, Small, and Medium Enterprises (MSMEs), with financing as a moderating variable. The research sample consists of 100 MSME owners or managers located in Gresik City, specifically in Gresik, Kebomas, and Manyar Districts, selected using purposive sampling based on predetermined criteria. Hypothesis testing was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software through a bootstrapping procedure and one-tailed testing. The results indicate that financial literacy and the use of accounting information have a positive and significant effect on MSME financial performance. In addition, financing is proven to strengthen the influence of financial literacy and accounting information on MSME financial performance. This study is expected to provide practical benefits for MSME actors in improving financial performance through better financial management and access to financing. The limitation of this study lies in the limited research area and the use of perception-based data.